Sodium laurate enhancements the thermal properties and thermal conductivity of eutectic fatty acid as phase change material (PCM) - Fauzi H.; Metselaar H.S.C.; Mahlia T.M.I.; Silakhori M. (2023)
One way to improve the thermal properties of myristic acid/palmitic acid (MA/PA) eutectic phase change material (PCM) is by adding an acid-based surfactant. The incorporation of surfactant into MA/PA eutectic mixture can significantly increase the latent heat storage capacity and decrease the subcooling of material. In this study, the preparation of myristic acid/palmitic acid (MA/PA) eutectic mixture with addition of 0%, 5%, 10%, 15%, and 20% sodium laurate (SL) as surfactant is reported and the influence of SL on thermal properties and thermal conductivity of the eutectic mixture is investigated. It was found that the addition of 10% SL to MA/PA eutectic mixture significantly lowered the phase transition temperature and the subcooling by 4.73°C and 0.43°C, respectively. In addition, the surfactant also increased the latent heat and the thermal conductivity to 15.14Jg-1 and 0.010Wm-1K-1, respectively. © 2013 Elsevier Ltd.